Upcycling from ‘One-of-a-Kind’ to Industry Scale: Leveraging Strategies to Prolong the Life of Industrial Waste Materials - Lund, Mathias; Laursen, Linda Nhu (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Industrial production generates waste in the form of scrapped, returned, or otherwise discarded materials, many of which are downcycled into lower-quality outputs. Upcycling offers a sustainable alternative by transforming waste into higher-value products while maintaining material integrity and leveraging more than just its basic composition. This study examines how product designers upcycle industrial scraps at an industrial scale. Through analysis of ten Danish field experiments with materials such as wood, concrete, leather, and fabric, we identified five leveraging strategies that distinguish the design processes of successful market entries from those that did not. These strategies are: (1) Linking the material to a portfolio to explore gaps and product line-up extensions, (2) Utilizing the material by leveraging locally available processing capabilities, (3) Shaping a by-product by adjusting ongoing production operations, (4) Leveraging the existing brand image, and (5) Leveraging 'Un-qualification as a Quality. The findings propose a framework for integrating upcycling into industrial contexts by strategically aligning products with company goals, resources, brand identity, and market position, to increase the likelihood of scaling upcycling from one-of-a-kind efforts to continued industrial practice.